The Governance of Island Tourism Management Strategies and Sustainable Development Plans, Sumenep, Madura - Riyadi, Slamet; Sufa, Siska Armawati; Baruno, Agustiawan Djoko; Christantyawati, Nevrettia; Priyambodo, Priyambodo (IJBLE Scientific Publications Community Inc., 2024)
This research delves into the intricate realm of island tourism governance, focusing on the Sumenep region of Madura, East Java, and its strategies for sustainable development. Utilizing an in-depth interview methodology, coupled with insights from tourism communication theory, the study aims to unravel the multifaceted dynamics that underpin the management of tourism on islands. Through interviews with key stakeholders such as government officials, community leaders, and industry representatives, this investigation sheds light on the governance structures, policies, and communication strategies that influence tourism management in the region. By synthesizing the perspectives and experiences of these stakeholders, the research endeavors to uncover the challenges, opportunities, and effective practices for sustainable island tourism development in Sumenep. Ultimately, this study not only enriches our understanding of tourism governance complexities but also offers actionable insights for policymakers, communities, and industry players to promote the sustainable growth of tourism in island destinations.